THE ROLE OF THE SAPARAN TRADITION IN STRENGTHENING SOCIAL INTERACTION AND INTERRELIGIOUS HARMONY IN POLOBOGO VILLAGE, SEMARANG REGENCY: Peran Tradisi Saparan Dalam Membangun Interaksi Sosial Dan Kerukunan Antarumat Beragama di Desa Polobogo Kabupaten Semarang - Avatar Amer Azzikra Avatar; Novia Wahyu Wardhani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Cultural and religious diversity in Indonesia often poses challenges in maintaining interfaith harmony due to differences in beliefs, values, and religious practices. This condition indicates that social harmony does not emerge naturally, but must be deliberately constructed through social practices within community life. In this context, this study examines the role of the Saparan tradition as a space for social interaction in maintaining interfaith harmony in Polobogo Village, Semarang Regency. This research aims to understand the processes, meanings, and dynamics of interfaith social interactions formed through the implementation of the Saparan tradition. The study employs an interpretive qualitative approach, using data collection techniques such as observation, interviews, and documentation. Informants were selected through purposive sampling and included community leaders, religious leaders, and residents actively involved in the Saparan tradition. Data validity was ensured through source, technique, and time triangulation. The findings indicate that the Saparan tradition functions not only as an annual cultural ritual but also as an effective space for social interaction among communities with diverse religious backgrounds. Through its stages of preparation, implementation, and closing, the tradition fosters social interaction, cooperation, and communication among residents regardless of religious differences. Moreover, the Saparan tradition embodies positive values that are actively practiced in everyday community life. Academically, this study contributes to the fields of cultural and religious sociology by affirming that local cultural traditions can serve as mechanisms for fostering harmony in pluralistic societies. These findings demonstrate that local wisdom holds significant potential in maintaining social diversity and interfaith harmony and can serve as a reference for future research on the role of local cultural traditions in multicultural societies.